SELF DEVELOPMENT IN PERSONALLY ORIENTED SPACE (Pedagogy of Higher and Secondary Education, 2022)
Article is devoted of the development of personality in historical perspective, as well as in combination with self-development through the personality-oriented training.
Keywords: personality-oriented education; self-determinatim; self-realization; personality-oriented lesson